Social capital and the reproduction of economic inequality in polarized societies - Mogues, Tewodaj; Carter, Michael R. (International Food Policy Research Institute, 2005)
This paper explores the idea of how wealth is distributed across social groups (ethnic or language groups, gender, etc.) and how such distribution fundamentally affects the evolution of economic inequality. By providing microfoundations suitable for this exploration, the paper hopes to enhance the understanding of when social forces contribute to the reproduction of economic inequality. In tackling this issue, the paper offers contributions in two domains. First, it models social capital as a real capital asset with direct use and collateral value. Second, it extends the concepts of identity, alienation and polarization used by Esteban and Ray (1994). This generalization permits consideration of the multiple characteristics that shape social identity, inclusion and exclusion. It also underwrites a higher-order measure of socioeconomic polarization that permits exploration of the hypothesis that economic inequality is most pernicious and persistent when it is socially embedded. Among other things the paper shows that holding constant the initial levels of economic polarization and wealth inequality, higher socioeconomic polarization increases subsequent income and wealth inequality. Far from being a distributionally neutral panacea for missing markets, social capital in this model may itself generate exclusion and deepen social and economic cleavages.